Developing ‘About Us’ and ‘Our Products’ pages for SME Batik’s owned media using applied genre framework - Anyassari, Nugrahaningtyas Fatma; Istifaiyah, Alda Imroatul; Agustina, Hiqma Nur; Indrianti, Titien; Rohani, Siti (Politeknik Negeri Jember, 2025)
Indonesian government policy on enhancing SMEs to go international needs support, also, from educational sector, as part of pentahelix. Potentials SME batik has and the problem in completing communication channels it is experiencing, this developmental study addresses. By employing design and development research (DDR), this study developed ‘about us’ and ‘our products’ pages by using applied genre as the framework. The pages were then published on owned media in the form of a website. Following ADDIE model as the research procedure, this study focused on the first three stages- analysis, design, and development-as this was an initial stage. The results of ‘about us’ and ‘our products’ pages were validated by two experts: language expert from a vocational higher institution and content expert from industry. The validation results show positive feedback from both experts in terms of relevance, understandability, language, reliability, adequacy, scope, usefulness, and multimodality. It leads to the possibility to apply applied genre not only in teaching language for specific purposes but also in solving SME batik’s business communication problems.